PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA CAFE KEBUN LATTE CIATER DI KOTA TANGERANG SELATAN - Wulansari, Retno; Dewi, Winda Kusuma (Yayasan Education and Social Center, 2024)
This reseach purposed to investigate the influence of brand image and promotion, partially and simultaneously, on purchase decisions at Café Kebun Latte in Ciater, Tangerang Selatan. Researcher used a quantitative methodology withhundred (100) respondents. And the sample was determined and used Rao Purba teory, and data were collected through questionnaires, and data analysis includedvalidity and reliability tests, classic assumption tests, multiple regression analysis,t-tests, F-tests, and determination coefficient calculations. The findings explained this study revealed that brand image had a significant partial effect on purchase decisions. This was supported by the calculated t-value resulted (2,976 > 1,984). From the simple linear regression analysis, the regression equation resulted Y = 9.447 + 1.548X1 was obtained, indicating a positive effect with a coefficient of 1.548. Promotion significantly influenced purchase decisions, as demonstrated by the calculated t-value resulted (8.439 > 1,984). The regression equation for promotion resulted Y= 10.187 + 1.075X2, with a positive effect indicated by a coefficient of 1.075. Furthermore, when considered simultaneously, both brand image and promotion had a significant and positive effect on purchase decisions, as resulted by the regression equation Y = 6.457 + 0.465X1 + 0.833X2. The hypothesis testing and F-value (186.775 > 3.09). The coefficient of determination (R-squared) was found about 0.794, indicating that 79,4% of the variability in purchase decisions was explained by the variables of Brand Image and Promotion. The remaining about 20.6% was influenced by onother factors. In conclusion, the results indicated that Brand Image and Promotion have a significant influence 79,4% on purchase decisions, while the remaining 20.6% was influenced by another factors